Penguatan toleransi beragama melalui tradisi tulun tali di Desa Sukutokan - Maria Inviolata Deran Ola; Petrus Tukan; Krisantus Minggu Kwen (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Indonesia has a lot of diversity, including ethnicity, culture, language, and religion. This divercity makes Indonesia a country ini rich in divercity. In responding to this diversity, of course there is an attitude of tolerance to prevent division. In the midst of this era of development, there is still a phenomenon of intolerance, so tolerance needs to be echoed and strengthened continuously. One of them in through the local tradition of tulun tali which is practiced by the people of Sukutokan Village, Kelubagolit District, on Adonara Island.This tradition is a praktice of mutual cooperation in terms of helping in the form of goods, foodstuffs and animals in people’s lives at certain events or events. This study aims to determine how to strengthen religious tolerance through the tulun tali tradition in Sukutokan Village. The research method used in this study is a qualitative using a descriptive approach. The results of study show that the tulun tali tradition practiced by the Sukutokan Village community in various social activities, such as death customs, marriages, religious events, building traditional house, and building residents house can strengthen religious tolerance.